2001
DOI: 10.1215/15228517-3-1-29
|View full text |Cite
|
Sign up to set email alerts
|

Adult medulloblastoma: Multiagent chemotherapy

Abstract: In this study, the records of 17 adult patients with medulloblastoma treated with craniospinal radiation and 1 of 2 multiagent chemotherapy protocols were reviewed for progression-free survival, overall survival, and toxicity, and the patients were compared with each other and with similarly treated children and adults. Records of patients treated at 3 institutions were reviewed. Seventeen medulloblastoma patients (11 female, 6 male) with a median age of 23 years (range, 18-47 years) were treated with surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 12 publications
2
23
0
1
Order By: Relevance
“…1,4,10,22,31,32,38,40 The distribution of histological variants was also comparable to that reported by other authors, 1,7,10,19,24,26,31,34,36,38,43 with predominance of the classic histological phenotype. However, our population showed some characteristics different from other series.…”
Section: Population Studysupporting
confidence: 90%
“…1,4,10,22,31,32,38,40 The distribution of histological variants was also comparable to that reported by other authors, 1,7,10,19,24,26,31,34,36,38,43 with predominance of the classic histological phenotype. However, our population showed some characteristics different from other series.…”
Section: Population Studysupporting
confidence: 90%
“…[9][10][11] An important recent retrospective analysis by 22 This study demonstrated that both increasing age and male gender were associated with significantly less toxicity using VIDE chemotherapy. In HL, females were reported to experience both greater toxicity and better survival than males, and the degree of neutropenia correlated with eventual outcome.…”
Section: Discussionmentioning
confidence: 80%
“…[6][7][8] Survival has been linked to treatment on paediatric protocols, 4 or to treatment at specialized paediatric centers. 6 It has been widely speculated that clinicians believe that adults tolerate treatment less well than children, [9][10][11] and chemotherapy dose intensity in adult acute lymphoblastic leukaemia (ALL) protocols was lower than in paediatric protocols. 4 Other contributing factors may include delayed clinical presentation and compliance issues.…”
mentioning
confidence: 99%
“…In 2000, Greenberg et al noted in a series of 17 adults that adults had higher rates of toxicity from chemotherapy, and 100% of adults required dose reductions during their course of treatment compared with 4.4% of children who were unable to complete treatment. 30,31 Thus, different treatment protocol and other unrecorded variables may be the source of the differences observed in this study.…”
Section: Discussionmentioning
confidence: 89%